The social media MBA : your competitive edge in social media strategy development & delivery - Holloman, Chister (Chichester, West Sussex, U.K. ; Hoboken, N.J : Wiley, 2012)
It's a fact that companies so far have only scratched the surface of what can be achieved with social media. Whatever continent, industry, company size, current degree of social media adoption or your job title, the purpose of this book is to inspire you to see how you can raise the bar further to reap new rewards. It will give you the tools to make a difference to your organisation's social media strategy development and delivery going forward. In addition it will also give you more intellectual support and confidence to discuss social media on a higher level with peers, inspire colleagues or negotiate and create support for increased investments from your leadership team. In The Social Media MBA editor Christer Holloman has crowd sourced 15 thought leaders from 4 continents to offer an exceptional educational programme written for experienced social media professionals just like you.
Includes index
BSBA
Keywords: Information technology -- Management; Social media; Customer relations; Internet marketing; Branding (Marketing)